Discovering computers complete : your interactive guide to the digital world - Shelly, Gary B.; Vermaat, Misty (Shelly Cashman series, 2012)
Students are guided through the latest trends in computer concepts and technology in an exciting and easy-to-follow format. Updated for currency, discovering computers: complete provides the most up-to-date information on the latest technology in today's digital world